Molar extrusion with fixed plateau appliance: clinical case report (Research, Society and Development, 2021)
Objective: The aim of this study was to report a clinical case of posterior teeth extrusion using a fixed plateau appliance with the aim of correction and alignment. Methodology: Based on the patient's permission through the Informed Consent Form (FICF) to share her image for the proper purpose, this study is a clinical case report of a descriptive analytical nature (Pereira et al., 2018). Clinical Case Report: Patient M.B.S.D.S., melanoderma, female, 11 years and 9 months, attended with her person responsible for FAMETRO: Integrated Child Care Clinic, for orthodontic treatment as indicated by the pediatric dentist. He presented good health conditions in general, without relevant systemic involvement. After anamnesis and clinical examination, cephalometric examinations, panoramic radiography, radiographic reports, intraoral photographs and profiles were requested. Final Considerations: In this way, the use of the device to correct deep bites is advisable, as this procedure can help the final facial esthetics.